Surveillance, control and management of infections in intensive care units in Southern Europe, Turkey and Iran--a prospective multicenter point prevalence study - Erdem, Hakan; Inan, Asuman; Altındis, Selma; Carevic, Biljana; Askarian, Mehrdad; Cottle, Lucy; Beovic, Bojana; Csomos, Akos; Metodiev, Krassimir; Ahmetagic, Sead; Harxhi, Arjan; Raka, Lul; et al. (Elsevier BV, 2014)
We aimed to compare the features of intensive care units (ICUs), their antimicrobial resistance patterns, infection control policies, and distribution of infectious diseases from central Europe to Mid-West Asia.
Keywords: ICU; Infection; Turkey; Europe; Iran; Resistance